Guest Editorial: Antenna-Enabled Sensors and Systems, the New Frontier in Sustainable Wireless Systems - Mahmoud Wagih; Gaetano Marrocco; Mohammad H. Zarifi; Jasmin Grosinger; Chaoyun Song; Qammer H. Abbasi (IEEE Open Journal of Antennas and Propagation, 2024)
Antennas are shifting with the Internet of Everything (IoE), 6G Joint Sensing and Communication (JSAC), and Wireless Power Transfer (WPT) paradigms into multifunctional devices, that provide more functionality than simply transmitting and receiving communication signals. Thus, antennas or RF-enabled devices [1], emerged as a class of IoE systems which use antennas as sensors, power supplies, or multi-functional JSAC interfaces. This editorial highlights the accepted contributions across 11 papers, presenting contributions from leading researchers on innovative antenna applications beyond telecommunication, spanning RFID, sensing applications in agriculture, food, healthcare, computational imaging, and wireless power transfer.